Death of a classified worker probably caused by overexposure to gamma radiation. Issue 10 (October 1994) - Lloyd, D C; Edwards, A A; Fitzsimons, E J; Evans, C D; Railton, R; Jeffrey, P; Williams, T G; White, A D; Ikeya, M; Sumitomo, H
Abstract : This paper describes the case of an industrial radiographer who was seriously overexposed to gamma radiation. The exact circumstances of this exposure were not established but it was concluded that he was repeatedly irradiated probably to a total average whole body dose of at least 10 Gy over several years. Also, a much larger dose to a hand required its partial amputation. He developed myelodysplasia, which progressed to acute myeloid leukaemia from which he died. Karyotypic examination of the leukaemic blasts showed changes very similar to those associated with secondary leukaemia that may develop after radio or chemotherapy. The paper describes his medical case history, the investigation of his workplace, and the attempts to estimate his radiation dose by chromosomal analysis of blood lymphocytes and electron spin resonance of dental enamel and bone.